Development of Microlearning-Based and Problem-Solving Infused English Reading Materials for Non-English Major: a Needs Analysis - Bontisesari; Dewanti, Ratna; Sulistyaningrum, Siti Drivoka (Asian Journal of Applied Education (AJAE), 2023)
This study aimed to analyse the English reading materials currently used by non-English major students and evaluate the extent to which they incorporate microlearning and problem-solving skills. The study was conducted at a public university in Bogor, Indonesia. The research utilized qualitative content analysis to examine a set of existing learning materials, consisting of a coursebook, PowerPoint slides, explainer videos, and infographics. Interviews with five English instructors were also conducted to explore the needs of learning materials further. The findings reveal a gap between the current materials and the descriptors of microlearning and problem-solving. Therefore, it indicates an urgency of developing new English reading materials that promote problem-solving and incorporate microlearning to facilitate the needs of non-English major students better.